Oral health is a mediator for disease severity in patients with Behcet's disease: A multiple mediation analysis study - AKSOY, AYSUN; ALİBAZ ÖNER, FATMA; MUMCU, GONCA; İNANÇ, GÜZİDE NEVSUN; DİRESKENELİ, RAFİ HANER; ERGUN, SAFİYE ATLAS TÜLİN (WILEY, 2019)
ObjectivesThe aim of the study was to examine whether oral health as an infection focus could mediate disease course in patients with Behcet's disease (BD). MethodsIn the study, oral health of 194 BD patients was examined at baseline and follow-up periods. The reasons for last dental visits were recorded as tooth extraction or regular control visits/planned treatments at the end of follow-up period. The Behcet's disease severity score was calculated with higher scores indicating a more severe course. Mediation analysis was carried out to assess the effects of oral health on disease severity score at follow-up period in the study. ResultsDental and periodontal indices were found to be higher at follow-up visit compared to those of baseline (P<0.05). Disease severity score was found to be higher in males (5.32.4) compared to females (4.4 +/- 2.5) in the whole group (P=0.005). Moreover, patients having tooth extraction at their last dental visit and patients with dental caries had a more severe disease course (5.4 +/- 2.4; 5.5 +/- 2.5) compared to others (4.2 +/- 2.3; 4.4 +/- 2.4; P<0.0001). In multiple mediation analysis, disease severity score was a dependent variable and was directly mediated by male gender (B=-0.8822, P=0.0145) and indirectly mediated through the presence of dental caries (B=0.9509 P=0.0110) and need of tooth extraction (B=0.8758, P=0.0128). ConclusionBoth presence of dental caries and need of tooth extraction were observed to be effective mediators for a more severe disease course in BD. Therefore, better oral health should be aimed to eliminate microbial factors, which are a part of pathogenic processes.
Keywords: Behcet's disease; gender; mediation analysis; oral health; oral hygiene education; treatment; PERIODONTAL FINDINGS; INFECTIOUS ETIOLOGY; SALIVARY LEVELS; ULCER ACTIVITY; HNP 1-3; ASSOCIATION; PATHOGENESIS; STRATEGIES